Using coordinate transforms to improve the utility of a fixed field of view high speed camera for additive manufacturing applications. (January 2018) - Scime, Luke; Fisher, Brian; Beuth, Jack
Abstract: Understanding in-situ melt pool dynamics has become a major research focus for the metals additive manufacturing community. Much of the research on melt pool dynamics in the Laser Powder Bed Fusion processes makes use of a high speed visible-light or infrared camera. Because these cameras are typically installed "after-market" on pre-existing AM machines they are often limited to a fixed field of view. This work presents a method for efficiently converting images captured by a high speed camera with a fixed field of view into a more useful format via a coordinate transform. Specifically, images of the melt pool are transformed such that they appear to have been captured with a camera integrated coaxially with the laser optic train.